Associations of rumen and rectum bacteria with the sustained productive performance of dairy cows - Yang, Jianhao; Li, Yifan; Sun, Mengkun; Zhang, Yuan; Guo, Shanshan; Zhou, Dong; Lin, Pengfei; Wang, Aihua; Jin, Yaping (Frontiers in Microbiology, 2025)
The gut bacterial community is essential for maintaining lifelong health and productivity in ruminants, but the relationship between the gut microbiota and the sustained productivity of ruminants remains inadequately understood. In this study, we selected long-lived dairy cows in mid-lactation (≥5 parities) with different levels of milk production (n = 10). Significant differences were observed in the rumen bacterial structures between the two groups of dairy cows, whereas no significant differences were detected in the rectum bacterial communities. Additionally, there were no significant differences in serum oxidative stress biomarkers, inflammatory markers, or immunological markers between the long-lived high-yield (LH) and long-lived low-yield (LL) dairy cows. Furthermore, the concentrations of propionate (Pr) in the rumen and butyrate (Bu) in the rectum were elevated in the high-yield group. Spearman correlation and microbial co-occurrence network analyses revealed that several rumen-enriched bacteria, such as Syntrophococcus, Lachnospira, Shuttleworthia, Erysipelotrichaceae_UCG-2, and Roseburiaare associated with rumen propionate (Pr) production. In the rectum, the reduced abundance of Christensenellaceae_R-7_group and Moryella favors butyrate production. Furthermore, Random Forest machine learning analysis demonstrated that six bacterial taxa in the rumen combined with one serum biomarker, as well as three bacterial taxa in the rectum combined with three serum biomarkers, can serve as potential biomarkers for distinguishing between LH and long- LL dairy cows, achieving prediction accuracies of 92 and 99%, respectively. The findings of this study indicate that rumen and rectum bacteria are associated with the milk production phenotypes of dairy cows with sustained productivity. The rumen microbes are closely linked to the long-term productive capacity of dairy cows and represent a key target for the development of gut microbiota-based interventions. The unique bacterial communities of the rumen and rectum of long-lived high-yielding dairy cows contribute to maintaining their productive capacity.